Sex Differences in Murine Susceptibility to Systemic Viral Infections - Geurs, Theresa L. (2011)
Increased susceptibility to autoimmunity in females is often viewed as the consequence of enhanced immunoreactivity providing superior protection against infections. We paradoxically observed greater mortality in female compared to male mice during systemic viral infections with three large double-stranded DNA viruses (herpes simplex virus type I [HSV], murine cytomegalovirus [MCMV], and vaccinia virus [VV]). Indeed, female mice were 27-fold more susceptible to infection with HSV than male mice. Elimination of estrogen by ovariectomy in female mice or addition of estrogen to castrated male mice only partially eliminated the observed sex differences following HSV infection. However, the differences observed in survival between female and male mice were nearly abrogated in the absence of type I interferon receptor signaling and substantially mitigated in absence of DAP12 signaling. Interestingly, the sex-specific impact of type I interferon receptor and DAP12 signaling differentially influenced survival during systemic viral infections with type I interferon receptor signaling enhancing male survival and DAP12 signaling increasing the susceptibility of female mice. These results have potential implications for the sex disparities observed in human autoimmune disorders.